Impact of Nano-Scale Distribution of Atoms on Electronic and Magnetic Properties of Phases in Fe-Al Nanocomposites: An Ab Initio Study - Miháliková, Ivana; Friák, Martin; Jirásková, Yvonna; Holec, David; Koutná, Nikola; Šob, Mojmír (Nanomaterials (Basel, Switzerland), 2018)
Quantum-mechanical calculations are applied to examine magnetic and electronic properties of phases appearing in binary Fe-Al-based nanocomposites. The calculations are carried out using the Vienna Ab-initio Simulation Package which implements density functional theory and generalized gradient approximation. The focus is on a disordered solid solution with 18.75 at. % Al in body-centered-cubic ferromagnetic iron, so-called α -phase, and an ordered intermetallic compound Fe 3 Al with the D0 3 structure. In order to reveal the impact of the actual atomic distribution in the disordered Fe-Al α -phase three different special quasi-random structures with or without the 1st and/or 2nd nearest-neighbor Al-Al pairs are used. According to our calculations, energy decreases when eliminating the 1st and 2nd nearest neighbor Al-Al pairs. On the other hand, the local magnetic moments of the Fe atoms decrease with Al concentration in the 1st coordination sphere and increase if the concentration of Al atoms increases in the 2nd one. Furthermore, when simulating Fe-Al/Fe 3 Al nanocomposites (superlattices), changes of local magnetic moments of the Fe atoms up to 0.5 μ B are predicted. These changes very sensitively depend on both the distribution of atoms and the crystallographic orientation of the interfaces.
Keywords: disorder; magnetism; Fe-Al; interfaces; stability; ab initio; Fe3Al